The retrospect of practical medicine and surgery (Simpkin, Marshall, and Co., 1840)
"Being an analysis of the British and foreign medical journals and transactions; or, a selection of the latest discoveries and most practical observations in the practice of medicine, surgery, and the collateral sciences, for the past year, made chiefly with reference to the treatment of disease."